The impact of service quality towards customer loyalty at Macy Home Furnishings / Nurkhairiyah Suhairi - Suhairi, Nurkhairiyah (Faculty of Business and Management, 2014)
These days all organizations are realizing the importance of service quality. This research is about the impact of service quality towards the customer loyalty at Macy Home Furnishing. One of challenges that face by Macy Home Furnishing is how they manage service quality which is important towards the customer loyalty. In order to investigate the relationship between service quality and customer loyalty at Macy Home Furnishing, there are some factor of service quality that will give affect towards customer loyalty have been identified. The survey will be conducted at Macy Home Furnishing by using descriptive research. The respondents will be selected among the customers who come to the venue to get the services at Macy Home Furnishing. In this research, the service quality is measured through perception of the customers toward the service quality of Macy Home Furnishing by using five dimensions of SERVQUAL which are tangible, reliability, responsiveness, assurance and empathy.